Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1210/jc.2005-2157
|View full text |Cite
|
Sign up to set email alerts
|

Mitotane Has an Estrogenic Effect on Sex Hormone-Binding Globulin and Corticosteroid-Binding Globulin in Humans

Abstract: Mitotane increased SHBG/CBG gene expression and liver production by mechanisms requiring the presence of ERalpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 22 publications
4
53
1
1
Order By: Relevance
“…In vitro studies showed that mitotane increases the synthesis of steroid binding protein (26,27). In our study, SHBG was markedly increased, whereas in males free T was decreased and LH was increased.…”
Section: Hormonal Parameterssupporting
confidence: 49%
“…In vitro studies showed that mitotane increases the synthesis of steroid binding protein (26,27). In our study, SHBG was markedly increased, whereas in males free T was decreased and LH was increased.…”
Section: Hormonal Parameterssupporting
confidence: 49%
“…It causes an increase in many binding globulins, including cortisol-binding globulin (CBG), which results in elevated plasma cortisol levels (152,153,154). For this reason, total serum cortisol level cannot be used to monitor the response to treatment or development of hypoadrenalism (152).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…This CYP3A4 induction can also, together with suppression of 11b-hydroxylase and cholesterol side chain cleavage, lead to hypocortisolism (Touitou et al 1978, Ghataore et al 2012. The adrenolytic effect of mitotane on the healthy contralateral adrenal, as well as enhanced production of cortisol-binding globuline in mitotane treated patients, also play a role in the occurrence of hypocortisolism (Nader et al 2006), which should be prevented by supraphysiological hydrocortisone replacement therapy.…”
Section: Current Therapeutic Strategiesmentioning
confidence: 99%